2021
DOI: 10.3390/w13212958
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients, Organic Matter, and Trace Elements in Lake Gusinoe (Transbaikalia)

Abstract: Lake Gusinoe is the second largest freshwater lake in Transbaikalia. Lakes serve as a source for drinking water, irrigation, and as a water source for the electricity, aquatic production, and tourism industry. Currently variations of content nutrients and organic matter differ in different areas of the lake. The content of total nitrogen, phosphorus, organic matter, and dissolved oxygen are distinguished more than 1.2–2.0 times. In accordance with the behavior of elements in the water, three groups of elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The findings from the study at the shallow Lake Ulansuhai, in central Mongolia, confirmed that ice cover can dramatically increase nutrient concentrations in water during the winter [22]. Higher concentrations of PO 3− 4 −P and NO − 3 −N were observed in ice-covered water during winter in Lake Arakhley [23] and Lake Gusinoe [24] in the Transbaikal Region of Russia. Powers et al [25] reported that the nitrate accumulation was strongly correlated to the number of days from the onset of ice cover in the temperate lakes Allequash, Big Muskellunge, Crystal, Sparkling, and Trout in North America.…”
Section: Introductionsupporting
confidence: 58%
“…The findings from the study at the shallow Lake Ulansuhai, in central Mongolia, confirmed that ice cover can dramatically increase nutrient concentrations in water during the winter [22]. Higher concentrations of PO 3− 4 −P and NO − 3 −N were observed in ice-covered water during winter in Lake Arakhley [23] and Lake Gusinoe [24] in the Transbaikal Region of Russia. Powers et al [25] reported that the nitrate accumulation was strongly correlated to the number of days from the onset of ice cover in the temperate lakes Allequash, Big Muskellunge, Crystal, Sparkling, and Trout in North America.…”
Section: Introductionsupporting
confidence: 58%
“…Comprehensive studies of surface and bottom waters, BSs, flora, and fauna have been conducted in the Lake Gusinoe basin to monitor and assess the ecological status of the aquatic environment [15,16,[19][20][21]. Numerous studies indicate an increase in anthropogenic pressure on the waters of the Gusinoe basin, which indicate changes in water flow, temperature regime, and land use; an increase in major ions in the water; and an increase in heavy metals in the water, bottom sediments, and higher vegetation.…”
Section: Introductionmentioning
confidence: 99%